SOSIALISASI OLAHRAGA TRADISIONAL DALAM RANGKA PEMAJUAN KEBUDAYAAN INDONESIA - Rachman, Fadlu; Armanjaya, Satria; Fajar Ramadhan, Ziko; Prasetiyo, Andri; Sari, Felinda; Nuruhidin, Ahmad; Gumay, Jovana Renaldy; Sodik, Alfan Nur (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Cultural advancement is an essential component of maintaining national identity, including the preservation of traditional sports that are being abandoned by the younger generation. This Community Service activity aims to increase students' knowledge and participation in traditional sports as a form of preserving local culture. The targets of the activity are students at three partner schools: SMAN 1 Gading Rejo, SMAN 2 Gading Rejo, and SMK Patria, who have not received direct learning about traditional sports. The implementation method includes education through interactive counselling, direct practice of various conventional games (engklek, running blocks, congklak, dompu), and provision of learning media such as modules, leaflets, and video documentation. Evaluation was carried out through participatory observation, questionnaires, and interviews with students and teachers. The results of the activity showed that 87% of students were new to and playing traditional games, while 92% expressed interest in playing them again. In addition, teachers welcomed this activity and saw its potential for integration into PJOK learning and extracurricular activities. It was concluded that the socialisation of traditional sports was effective in fostering cultural awareness and students' love for local heritage. It is hoped that this activity can be replicated in other schools as part of the strategy to advance Indonesian culture.